A faithful sea. The religious cultures of the mediterranean, 1200-1700. Edited by Adnan A. Husain and K.E. Fleming, Oneworld Publications, Oxford, 2007.ISBN: 1851684964 / 1-85168-496-4, 226 p. - Samsó, Fernanda (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Centro de Estudios Filosóficos Medievales., 2010)

(untitled)
Fil: Samsó, Fernanda. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras